Optimizing Maternal and Child Health Through Basic Care Training - Junaidi; Ruslan Hasani; Ambo Dalle; Andi Ruhban (Indonesian Journal of Community Engagement, 2025)
This community service program was implemented to improve community knowledge and skills regarding basic maternal and child care in Karunrung Village, Makassar City. Key issues identified included limited access to health education, low awareness of the importance of basic care, and urban environmental conditions that do not support optimal health practices. To address these issues, the program employed a participatory approach through community-based counseling, training, and mentoring involving health workers and pregnant women. Educational activities covered maternal and child nutrition, pregnancy danger signs, personal and environmental hygiene, and infectious disease prevention. Practical training was provided through demonstrations of basic care techniques, including handwashing and infant care practices. Evaluation using pre- and post-tests demonstrated significant improvements in all aspects of knowledge; all participants achieved a good knowledge category after the training. The evaluation design used a pre-post-intervention approach without a control group to directly assess changes in knowledge. In addition, the program increased the capacity of health workers through facilitator training and the establishment of a communication network connected to community health centers for ongoing mentoring. Overall, the program proved effective in optimizing knowledge and skills regarding basic maternal and child care in urban settings. The intervention also successfully strengthened the role of cadres as health education agents in the community and improved public health literacy in general. These findings support the importance of a community-based approach to improving maternal and child health, particularly in densely populated areas with limited access to information.